PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP KINERJA MELALUI KEPUASAN KERJA DENGAN MODERASI MODAL PSIKOLOGI DAN PERSON-ORGANIZATION FIT (P-O FIT) (Studi Pada Dinas Pendidikan Kabupaten Rembang) - Dian Mariski, 13520220066; Soliha, Euis (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect, job characteristics, job satisfaction, through psychological capital and PO Fit employee to employee performance. The data used in this study are primary data taken with a list of statements given to employees of the Department of Education Rembang total of 103 respondents. Once the data is collected test responder test instruments and test regression. The test results showed all instruments are valid and reliable. The results showed: 1) employment characteristics influence on job satisfaction in the study had a fairly strong correlation and significant. 2) Characteristics of employment affect the performance in the study correlated quite strongly and significantly strong and significant, 3) Job Characteristics affect the performance in the study correlated quite strongly and significantly strong and significant, 4) Capital Psychology moderate but weaken Satisfaction Work, 5). PO-Fit moderate job satisfaction to Performance.Keywords: Job Characteristics, Job Satisfaction, Performance, Capital Psychology, and Person-Organization Fit